Associations of Participation in Organized Sport and Self-Organized Physical Activity in Relation to Physical Activity Level Among Adolescents - Pål Lagestad; Hilde Mikalsen; Laura Suominen Ingulfsvann; Idar Lyngstad; Camilla Sandvik (Frontiers Media S.A., 2019)
Although physical activity level (PAL) is positively correlated with adolescents' health, many adolescents do not fulfill recommendations for physical activity. This study examines the associations of organized sport and self-organized physical activity, with PAL among adolescents. Participants were 301 adolescents (12-13 year-olds). The adolescents wore accelerometers for 1 week according to international standards, and reported their participation in organized sport and self-organized physical activity in a questionnaire. The results showed that the level of participation in organized sport was positively associated with the adolescents' total PAL, while there was no significant association between time spent in self-organized physical activity and adolescents' daily minutes of moderate and vigorous physical activity. In addition, boys who participated <3 h per week (or not at all) in organized sport stood out with the lowest fulfillment of recommended PAL. Our findings underline the critical importance of getting adolescents, especially boys, to participate in organized sport and not to drop out from organized sport during adolescence.